Integrating serological and genomic data to elucidate lumpy skin disease virus diversity in cattle from Bangladesh - Nasrin Sultana Tonu; Sajedul Hayat; Shukes Chandra Badhy; Salima Ferdows; Md. Golam Azam Chowdhury; Babu Kanti Nath; Md Safiul Alam Bhuiyan; Muhammad Jasim Uddin; Suman Das Gupta; Subir Sarker (MDPI, 2025)
Lumpy skin disease virus (LSDV), a transboundary pathogen threatening cattle health in South and Southeast Asia, presents growing challenges for disease control. This study combined serological, molecular, and genomic approaches to investigate LSDV in Barura Upazila, Bangladesh. Serological screening of 424 cattle using a commercial ELISA revealed a high seroprevalence of 55.5% (95% CI: 50.7–60.3), indicating widespread exposure. Although differences were observed by age and breed, no significant associations were found with seropositivity, suggesting broad regional circulation. Real-time PCR confirmed LSDV DNA in all 20 clinically infected animals, with consistent P32 gene amplification. Two samples with low Cq values underwent whole-genome sequencing. The complete genomes of LSDV-L2/2024 and LSDV-L3/2024 showed >99.6% identity with the reference strain LSDV-29, yet carried unique genomic features, including truncated or variant ORFs and immune-related gene differences. Phylogenetic analysis of the DNA polymerase gene revealed distinct clustering: L2/2024 aligned with South Asian isolates, while L3/2024 grouped with strains from Africa, the Middle East, and Europe. These results highlight co-circulation of genetically diverse strains and possible cross-regional introductions. Over- all, our findings underscore the evolutionary plasticity of LSDV and the critical need for ongoing genomic surveillance to guide targeted vaccine development and disease control strategies